Рrofessional training of agents performing social and pedagogical support of minor offenders in the conditions of reforming of penal system in Ukraine - Анголенко, В. В. (Scientific notes of the pedagogical department, 2018)
In article questions of professional training of future workers of the social sphere as leading agents of social and pedagogical support of the minors exonerated with probation have been considered; the importance of the problem under consideration in connection with the essential growth of performance of illegal behavior among young people has been proved; scientific approaches to understanding of the concepts "training", "professional training" which are taken as a basis by the author for determination of essence of professional training of future workers of the social sphere for implementation of social and pedagogical support of minor offenders have been analyzed; the professional competence of future workers of the social sphere is defined as result of the appropriate professional training; the importance of the problem under components of professional competency: the cognitive component characterizes the theoretical knowledge gained in the course of mastering a profession from fundamental concepts in modern theories and concepts of social work; the motivational and valuable component acts in the form of set of subjective indicators of activity. These include requirements, motives, interests, directives, valuable orientations, orientation of the personality, ideals, etc. The motivational and valuable component includes presence in future worker of the social sphere of steady interest in obtaining additional knowledge, abilities and practical experience of social and pedagogical support of the minor offenders exonerated with probation; the pragmatist and practical component is characterized by formation by future experts of the social and pedagogical abilities necessary for work with minor offenders. Future worker of the social sphere must be able to develop and to effectively apply the social technologies considering features of a modern combination of gender equality and specifics of sociocultural development of the minor for ensuring his social health.